2011
DOI: 10.1093/nar/gkr017
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide quantitative assessment of variation in DNA methylation patterns

Abstract: Genomic DNA methylation contributes substantively to transcriptional regulations that underlie mammalian development and cellular differentiation. Much effort has been made to decipher the molecular mechanisms governing the establishment and maintenance of DNA methylation patterns. However, little is known about genome-wide variation of DNA methylation patterns. In this study, we introduced the concept of methylation entropy, a measure of the randomness of DNA methylation patterns in a cell population, and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 36 publications
3
103
0
Order By: Relevance
“…Similar conclusions apply to gene regions close to TSS vs. those further away from TSS. Consistent with a recent study on DNA methylation entropy, 38 our results indicated that methylation variation could be loci-specific and associated with the functional aspects of the corresponding genomic sequences. Higher inter-individual variations in the CpG shores and shelves and in TSS1500 indicated that these features were possibly more likely to be influenced by environmental factor exposure in utero and during early life, and thus could be strong candidates for disease differential methylation regions (DMR).…”
Section: Resultssupporting
confidence: 92%
“…Similar conclusions apply to gene regions close to TSS vs. those further away from TSS. Consistent with a recent study on DNA methylation entropy, 38 our results indicated that methylation variation could be loci-specific and associated with the functional aspects of the corresponding genomic sequences. Higher inter-individual variations in the CpG shores and shelves and in TSS1500 indicated that these features were possibly more likely to be influenced by environmental factor exposure in utero and during early life, and thus could be strong candidates for disease differential methylation regions (DMR).…”
Section: Resultssupporting
confidence: 92%
“…Further, the pattern of methylation loss at Alu elements is suggestive of an alteration in nucleosome positioning at the 59 and 39 ends of these elements, consistent with a global alteration in chromatin architecture. It is also conceivable that the DNA methylation changes observed here reflect a shift from homogenous to heterogeneous methylation patterning as previously described (Xie et al 2011).…”
Section: Discussionsupporting
confidence: 70%
“…The percentage of hemi-methylated CpG dyads varies considerably among these genomic segments and different cell types. On a genome-wide scale, extremely high fidelity on DNA methylation transmission was found for ;30% of genomic segments derived from CGIs and 10% of segments from Alu repeats, whereas only a small subset of CGIs and Alu elements have highly variable methylation patterns (Xie et al 2011). Notably, the methylation fidelities of CGIs and repetitive elements decrease in tumor tissues (Ushijima et al 2005;Watanabe et al 2006;Xie et al 2011).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…On a genome-wide scale, extremely high fidelity on DNA methylation transmission was found for ;30% of genomic segments derived from CGIs and 10% of segments from Alu repeats, whereas only a small subset of CGIs and Alu elements have highly variable methylation patterns (Xie et al 2011). Notably, the methylation fidelities of CGIs and repetitive elements decrease in tumor tissues (Ushijima et al 2005;Watanabe et al 2006;Xie et al 2011). Epigenetic instability in embryonic stem cells has also been well documented (Humpherys et al 2001;Minoguchi and Iba 2008).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%